ANALISIS KETIMPANGAN PEMBANGUNAN PROVINSI BANTEN PASCA PEMEKARAN - Wahyu Dhyatmika, Ketut; Dwi Atmanti, Hastarini (Diponegoro Journal of Economics, 2013)
This research aims to 1) analyze the magnitude of the inequality of development that happens in Banten Province after the expansion region;2)classifythe regency/municipalities based on Klassen typology; 3) analyze the influence of foreign direct investment (FDI), government expenditure (GE), and unemployment rate (UE) of inequality of development. Post expansion region in 2000,economic growth banten province tended to increase but followed with inequality will also increase.This research use 1) williamson Index, 2) Klassen typology, and 3) Analysis of panel data by method fixed effectÂ model (FEM) with the time research 2001-2011. The results showed that the level of inequality in Banten Province development tend to increase. Based on klassen Typology, tangerang and cilegon municipality is at a group of regional forward and fast growing, tangerang to a group of developing areas quickly and other areas located in the prologue and the left.Â Panel data analysis results with the method of FEM, foreign direct investment (FDI) and governmentÂ expenditure affect positif and negative against inequality, while the unemployment rate variable has no effect against the inequality of development in Banten Province after the expansion region.